Efficacy of groundnut haulm compost on the growth and yield of blackgram (Vigna mungo L.) var. Vamban 1 - T. Ravi Mycin2, P. Indira1, M. Lenin2 and (Current Botany, 2010)
<span style="font-family: Byington; font-size: 8pt; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Crop residues are the non-economic plant parts that are left in the field after harvest. The harvest refuses include straws, stubble, Stover and haulms of different crops.Â Crop remains are also from thrashing sheds or that are discarded during processing this includes process wastes like groundnut shell. The greatest potential as a biomass resource appears to be from the field residues of some crop plants in Tamil Nadu. The present study was undertaken to the groundnut haulm, was to evaluate the effects of organic compost on growth and yield of blackgram. The morphological parameters such as root length, shoot length, fresh weight, dry weight, number of leaves, number of root nodules and yield parameters were increased in all the haulm compost treated soil when compared to control.Â Among the sources the groundnut haulm compost applied plants for higher growth and yield than in others.